1983
DOI: 10.1017/s0317167100044875
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Radiculopathies by Segmental Stimulation and Somatosensory Evoked Potentials

Abstract: SUMMARY:Thirty-six patients with suspected or myelographically proven radiculopathies were investigated with motor and sensory conductions, F-waves, needle electromyography, and somatosensory evoked potentials (SEPs). SEPs were elicited by cutaneous nerve stimulation representative of input from individual cervical and lumbosacral dorsal roots. A myelographic defect was present in 83% of 30 patients who had myelograms. Overall 78% of patients had one or more abnormal electrophysiologic tests, the needle EMG gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(32 citation statements)
references
References 20 publications
4
26
1
1
Order By: Relevance
“…In a study of radiculopathies using soma tosensory potentials, which were evoked after segmental stimulation [10], a high diagnostic yield was obtained. However, we do not think that measurement of somatosensory evoked potentials should be the method of first choice for patients suffering from a ra dicular syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of radiculopathies using soma tosensory potentials, which were evoked after segmental stimulation [10], a high diagnostic yield was obtained. However, we do not think that measurement of somatosensory evoked potentials should be the method of first choice for patients suffering from a ra dicular syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of 11 rellexes [4,6). F waves [7][8][9], and somatosensory evoked potentials [10] can be helpful in this respect. The elic iting of H rellexes.…”
Section: Introductionmentioning
confidence: 99%
“…Eisen and coworkers found that 16 (57%) of 28 patients studied by this technique had abnormal scalprecorded responses, but NEE had the best diagnostic yield (75%). 28 The most common SEP abnormalities were reduced amplitude and poor morphology; latency abnormalities were uncommon. Using a similar technique, Perlik and associates evaluated the L4, L5, and S1 segments of 27 patients with low-back pain, unilateral radicular symptoms, and abnormal computerized tomography (CT) scans.…”
mentioning
confidence: 99%
“…Sensitivity to diagnose P1 latency prolongation in mixed sensorimotor nerves has been assumed to be reduced in monoradicular nerve root compromise because the evoked response may be conducted through a normal neighboring nerve root and the P1 latency may be normal [7,8,19,20]. The segmental specificity of the sensory nerves used for stimulation in the present study is better than that of mixed nerves, but is not perfect [5,18,19,40].…”
Section: Discussionmentioning
confidence: 74%